2013
DOI: 10.1128/aac.02474-12
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Fe Uptake Systems and AmpC β-Lactamase in Susceptibility to the Siderophore Monosulfactam BAL30072 in Pseudomonas aeruginosa

Abstract: BAL30072 is a monosulfactam conjugated with an iron-chelating dihydroxypyridone moiety. It is active against Gram-negative bacteria, including multidrug-resistant Pseudomonas aeruginosa. We selected mutants with decreased susceptibilities to BAL30072 in P. aeruginosa PAO1 under a variety of conditions. Under iron-deficient conditions, mutants with overexpression of AmpC ␤-lactamase predominated. These mutants were cross-resistant to aztreonam and ceftazidime. Similar mutants were obtained after selection at >1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…The fecI gene is an extracytoplasmic function (ECF) sigma-70 factor that acts as a transcriptional activator of the ferric citrate siderophore system (22). Mutations at this pfecI location have been reported for BAL30072-resistant isolates, and it was shown that by derepressing the fecIRA operon, a mutation in the Fur-binding promoter of fecI led to increased expression of the ferric citrate siderophore receptor FecA (20). Transcriptional analysis of our C2-ARC3502 pfecI mutant yielded the same result of elevated fecA expression relative to the parent (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fecI gene is an extracytoplasmic function (ECF) sigma-70 factor that acts as a transcriptional activator of the ferric citrate siderophore system (22). Mutations at this pfecI location have been reported for BAL30072-resistant isolates, and it was shown that by derepressing the fecIRA operon, a mutation in the Fur-binding promoter of fecI led to increased expression of the ferric citrate siderophore receptor FecA (20). Transcriptional analysis of our C2-ARC3502 pfecI mutant yielded the same result of elevated fecA expression relative to the parent (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…For five mutants, a variety of genetic changes were seen in the piuA and piuC genes, including insertions, deletions, and frameshifts all likely to result in a loss of function of the encoded proteins. PiuA is an outer membrane siderophore receptor with similarity to the Fiu catechol receptor, while PiuC is a predicted Fe(II)-dependent oxygenase with its gene located directly adjacent to PiuA (19,20). The predicted effect of a piuA or piuC mutation is decreased expression of the PiuA receptor, which is one of two receptors that hydroxypyridinone-based siderophore conjugates are believed to exploit for entry, with the other being PirA (20,21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The close phylogenetic relationship between Acinetobacter and Pseudomonas prompted us to search in A. baumannii for orthologues of the previously identified TonB-dependent receptors PiuA and PirA from P. aeruginosa (15,31). For each of these proteins, we identified one orthologue (Ͼ40% amino acid identity).…”
Section: Discussionmentioning
confidence: 99%
“…This monocyclic ␤-lactam contains an iron-chelating dihydroxypyridone substituent. Using a transcriptome approach, the FecIRA Fe 3ϩ -dicitrate transporter was identified as a regulatory cascade, and the PiuA iron receptor was identified as a putative uptake system affecting susceptibility to BAL30072 (3). The molecule has potent in vitro activity against many species of MDR isolates of the Enterobacteriaceae family, including isolates harboring a class A carbapenemase or a metallo-␤-lactamase (4,5).…”
mentioning
confidence: 99%